THE STUDIES AND EXAMINATIONS ON CARL BAERMANN VOLLSTÄNDİGE CLARİNET–SCHULE OP.63 EDUCATİON METHOD ABOUT CLARINET TEACHING METHODS - Kaya KILIÇ (Fırat University, 2019)
One of the most important factors while learning to play an instrument correctly is the source being used. In clarinet teaching methods and study, practice period is fundamental for playing the instrument. The development period and study method of every student or performer differ. During this period, planning, study schedule, study tactics, patience, study duration and order is important. Carl Baermann Op.63 numbered method, which is written for clarinet instrument, is a major source for guide and performer during this period. Having a world-famous virtuoso father helped Baermann on creating his own methods about clarinet techniques and difficulties. The Op.63 method subjected to this journal has different releases by two different editor and publisher. The differences between the releases are also stated in the journal. The method has 190 pages and 3 sections. Each of the sections has its own different practices and guides the technical and musical development of the performer. The first section is named as Historical and Theoretical structure, the second section is named as Preparatory Studies, and the third section is named as daily Studies. Due to the technical difficulties, it is recommended to start from the first section for performers. This journal is an important preparatory material for clarinet students and performers. İt is aimed to contribute to clarinet education. Besides, this study is considered important in respect to being a source to researches on clarinet teaching methods and helping clarinet performers.